Webbots, spiders, and screen scrapers : a guide to developing Internet agents with PHP/CURL - Schrenk, Michael (Safari Books Online., 2007)
The Internet is bigger and better than what a mere browser allows. Webbots, Spiders, and Screen Scrapers is for programmers and businesspeople who want to take full advantage of the vast resources available on the Web. --from publisher description.